2012
DOI: 10.1073/pnas.1121524109
|View full text |Cite
|
Sign up to set email alerts
|

Cold-inducible RNA-binding protein (Cirp) interacts with Dyrk1b/Mirk and promotes proliferation of immature male germ cells in mice

Abstract: Cold-inducible RNA-binding protein (Cirp) was the first cold-shock protein identified in mammals. It is structurally quite different from bacterial cold-shock proteins and is induced in response to mild, but not severe, hypothermia. To clarify the physiological function of Cirp in vivo, we produced cirp -knockout mice. They showed neither gross abnormality nor defect in fertility, but the number of undifferentiated spermatogonia was significantly reduced and the recovery of spermatogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 40 publications
2
102
0
Order By: Relevance
“…In Xenopus, CIRBP displays nucleocytoplasmic shuttling and has distinct roles in each cellular compartment (Aoki et al 2002). Nuclear CIRBP is associated with cell growth and differentiation (Lleonart 2010;Emmanuel et al 2011;Masuda et al 2012). In response to various environmental stressors, CIRBP moves from the nucleus to the cytoplasm where it associates with stress granules to regulate RNA metabolism (Yang and Carrier 2001;De Leeuw et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In Xenopus, CIRBP displays nucleocytoplasmic shuttling and has distinct roles in each cellular compartment (Aoki et al 2002). Nuclear CIRBP is associated with cell growth and differentiation (Lleonart 2010;Emmanuel et al 2011;Masuda et al 2012). In response to various environmental stressors, CIRBP moves from the nucleus to the cytoplasm where it associates with stress granules to regulate RNA metabolism (Yang and Carrier 2001;De Leeuw et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Genes-Because we found that siRNA against Cirbp sensitizes the cells to the effect of TNF to suppress Dbp mRNA, we analyzed the expression of clock genes in (MEFs), which were established from mice with an inactivation of the Cirbp gene (Cirbp Ϫ/Ϫ MEFs) (27). Compared with WT MEFs, the effect of TNF to lower the expression of clock genes was found to be more pronounced in Cirbp Ϫ/Ϫ MEFs (Fig.…”
Section: Cells With An Inactivation Of the Cirbp Gene Respond To Tnf mentioning
confidence: 99%
“…Subsequently blotting on a PVDF membrane was performed in a full wet tank blot. Membranes were incubated with a CIRBP rabbit polyclonal antibody recognizing the C terminus of mouse CIRBP (27). As secondary antibody an HRP-conjugated goat anti-rabbit (ab79051; Abcam) was used and incubated for 1 h. As a loading control an antibody to the mouse nuclear matrix protein p84 was used (1 h, ab487).…”
Section: Treatment Of Cells With Cytokines and Blockers-nih-3t3mentioning
confidence: 99%
“…The generation of Cirp À/À mice has been described previously (28 Isolation of lamina propria cells was performed as described previously (29). The isolated cells were sorted using immunomagnetic beads coated with monoclonal antibodies against CD11b (MACS Beads, Miltenyi Biotec) with the help of a separation column and a magnetic separator from the same company in accordance with the manufacturer's recommendations for isolating murine macrophages.…”
Section: Mice and Treatmentmentioning
confidence: 99%
“…The following antibodies were used: anti-actin and anti-DCAMLK1 (Dclk1) from Sigma-Aldrich; anti-Bcl-2, anti-phospho-IkBa, antiIkBa, anti-phospho-ERK, anti-ERK, anti-Sox2, anti-E-cadherin, anti-PCNA from Cell Signaling; and anti-F4/80 from eBioscience. Generation of anti-Cirp polyclonal antibody was previously described (28). Immunohistochemistry was performed using ImmPRESS reagents (Vector Laboratory) according to the manufacturer's recommendations.…”
Section: Biochemical and Immunochemical Analysesmentioning
confidence: 99%